Chondrocyte apoptosis: a cause or consequence of osteoarthritis? - Zamli, Zaitunnatakhin; Sharif, Mohammed (Wiley-Blackwell Publishing Asia, 2011)
Osteoarthritis (OA) is a degenerative joint disease characterized by articular cartilage degradation and changes in the subchondral bone. Over the last two decades, there has been increasing evidence showing association between cartilage degradation and chondrocyte death, and different types of cell death in cartilage have been reported, including apoptosis and chondroptosis as well as necrosis, but which of these types of cell death predominate in OA is debatable. There are also some methodological difficulties in detecting the specific form of cell death in articular cartilage. Current ‘gold standard’ for detecting chondrocyte death is electron microscopy which suggests that the morphological changes of chondrocytes in OA cartilage are attributed to apoptosis and/or chondroptosis. However, the current literature appears to suggest that classic apoptosis plays an important role in OA; but whether chondrocyte apoptosis is a cause or a result of cartilage degeneration in OA is hotly contested. Studies of suitable animal models, especially longitudinal studies, are needed to address the cause-and-effect relationship.